Controle de frequência de geração fotovoltaica considerando inércia virtual - RAMOS, Vanessa Menezes (Universidade Federal do Pará, 2018)
The large-scale integration of intermittent sources of renewable energies, such as photovoltaic systems, into electrical power systems generates new technical issues, since such sources do not participate in frequency regulation because they do not exhibit inertia of rotation. The rapid frequency variation, normally found in networks with a high degree of integration of renewable generation, therefore causes greater difficulty in maintaining frequency stability, unlike conventional systems (for example Hydro and Thermal), where the inertia of the generators is sufficiently high , for most of these new systems this is not valid. In this context, the present dissertation will propose the use of the concept of "virtual inertia", which corresponds to a combination of control algorithms, electrical energy storage devices and power electronics applied to renewable sources, such as photovoltaics, connected to networks of power through inverters, which emulates the inertia of a conventional generation system. It will be presented a model based on a small linearized signal analysis, developed to evaluate the stability of a power control circuit when the photovoltaic generator provides frequency response and the inertial response emulated with photovoltaic systems by means of techniques based on the MPPT controller in the Displacement Method and the Droop control strategy in the time domain. This modeling is tested in an electric power system composed of synchronous machines and a large-scale photovoltaic power generation plant for the analysis of the effects of the control system in relation to frequency stability. The simulations performed with MATLAB/Simulink software consider different inertia constants for a condition of variation (decrease) in the electric frequency, caused by the insertion of loads in the electric system. Comparative results indicate that the impact of photovoltaic generation on the stability of the power system is greater when the power supplied by the conventional plant generator is lower. Results also prove that when the photovoltaic system is supplying power to the grid, its frequency decreases, affecting the stability and operation of the power system through the degradation of the frequency dynamics.